Ligand binding induces agonistic-like conformational adaptations in helix 12 of progesterone receptor ligand binding domain - Zheng, Liangzhen (2019)
Progesterone receptor (PR) is a member of the nuclear receptor (NR) superfamily and plays a vital role in the female reproductive system. The malfunction of it would lead to several types of cancers. The understanding of conformational changes in its ligand binding domain (LBD) is valuable for both biological function studies and therapeutically intervenes. A key unsolved question is how the binding of a ligand (agonist, antagonist, or a selective modulator) induces conformational changes of PR LBD, especially its helix 12. We applied molecular dynamics (MD) simulations to explore the conformational adaptations of PR LBD with or without a ligand or the co-repressor peptides binding. From the simulations, both the agonist progesterone (P4) and the selective PR modulator (SPRM) asoprisnil induces agonistic-like helix 12 conformations (the “closed” states) in PR LBD and the complex of LBD-SPRM is less stable, comparing to the agonist-liganded PR LBD. The results, therefore, explain the partial agonism of the SPRM, which could induce weak agonistic effects in PR. We also found that co-repressor peptides could be stably associated with the LBD and stabilize the LBD in a “semi-open” state for helix 12. These findings would enhance our understanding of PR structural and functional relationships and would also be useful for future structure and knowledge-based drug discovery.